Textile characteristics of the Huacaya alpaca fibre, according to agroecological zones, sex and age in the Puno Region (Peru) - Larios-Francia, Rosa (2023)
The aim of this study was to evaluate the effect of the agroecological zone on the textile characteristics of the alpaca fibre (Vicugna pacos) from herds of productive units of the dry Puna and wet Puna in the Puno region, according to sex and age. The samples were obtained from 5530 Huacaya alpacas. Fibre diameter (FD), Standard Deviation of Fibre Diameter (SDFD), Coefficient of Variation of Fibre Diameter (CVDF), Spin Fineness (SF), Curvature Index (ICur) and Standard Deviation of Curvature Index (SDICur) were recorded using the OFDA 2000 equipment. The effects of the agroecological zone in relation to sex and age (Deciduous teeth [DL], 2 teeth [2D], 4 teeth [4D] and all teeth [BLL]) were estimated using a randomized design with factorial arrangement and Duncan's multiple range test. The FF values are in the range of 13.3 to 34.5 μm with an average value of 20.32 μm. The alpacas from the wet Puna presented lower FD (13.3-34.5 μm) compared to those from the dry Puna (13.6-37.9 μm). Age and sex affect the FD, as BLL alpacas registered a higher FF compared to the DL alpacas (p<0.05). Likewise, a lower FD was observed in male alpacas compared to females (p<0.05). The correlation between agroecological zones, sex and age was demonstrated by obtaining a smaller diameter in male DL alpacas from wet Puna. In addition, a significant correlation was identified between the fibre quality evaluated from its textile characteristics with the agroecological zone.